TEACHER'S ROLE IN MOTIVATING STUDENTS - Sodikova Yulduz Furkatovna (Zeta Repository, 2023)
Many factors motivate students to study. These factors may be internal or external. This article discusses the role of the teacher in motivating students to learn. The literature on learning and motivation reveals ways teachers can increase students' motivation to learn. Although students may have an innate desire to learn, the external support provided by the teacher has a significant impact on student learning. The teacher's role in motivation includes but is not limited to creating an environment conducive to learning.